2022
DOI: 10.3389/fonc.2022.931209
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analyses unveil novel genomic and immunological characteristics of micropapillary pattern in lung adenocarcinoma

Abstract: Lung adenocarcinoma (LUAD) usually contains heterogeneous histological subtypes, among which the micropapillary (MIP) subtype was associated with poor prognosis while the lepidic (LEP) subtype possessed the most favorable outcome. However, the genomic features of the MIP subtype responsible for its malignant behaviors are substantially unknown. In this study, eight FFPE samples from LUAD patients were micro-dissected to isolate MIP and LEP components, then sequenced by whole-exome sequencing. More comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Our results also found one lepidic (1/3) and one micropapillary lung adenocarcinoma sample (1/3) existed TP53 mutation, but not found KRAS, PIK3CA mutations and ALK rearrangements, which maybe attribute to small sample size. As reported previously [8, 34, 10], several novel genes mutation were identi ed in micropapillary lung adenocarcinoma, such as ZNF469, TTN, TENM4, APOBEC, KEAP1, NOTCH4, PTP4A3, NAPRT, and RECQL4 [8, 34,10]. Further studies discovered that these novel genes were regarded as oncogenes or tumor suppressor genes and had played a pivotal role in the progression and prognosis of lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Our results also found one lepidic (1/3) and one micropapillary lung adenocarcinoma sample (1/3) existed TP53 mutation, but not found KRAS, PIK3CA mutations and ALK rearrangements, which maybe attribute to small sample size. As reported previously [8, 34, 10], several novel genes mutation were identi ed in micropapillary lung adenocarcinoma, such as ZNF469, TTN, TENM4, APOBEC, KEAP1, NOTCH4, PTP4A3, NAPRT, and RECQL4 [8, 34,10]. Further studies discovered that these novel genes were regarded as oncogenes or tumor suppressor genes and had played a pivotal role in the progression and prognosis of lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 62%
“…To get a better explanation for the underlying mechanisms beyond tumorigenesis and malignant discrepancy, several studies were performed to assess the molecular mechanisms and genetic changes of LUAD subtypes, especially on micropapillary lung adenocarcinoma [8][9][10][11]. Two recent studies indicated that patients with micropapillary components had induced the disruption of the catenincadherin complex, contributing to its intracellular adherence [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The multivariate Cox analysis showed that smoking history, MIP components, and GGO components were independent prognostic factors affecting patients’ RFS; however, when the GGO component was included in the analysis, the MIP component exhibited no significant correlation with patients’ CSS. EGFR mutations are reported to be the most common mutation in Asian populations, accounting for more than 70% of lung adenocarcinomas containing MIP components ( 31 , 32 ). In our study population, a total of 37 patients developed local recurrence and distant metastasis after surgery, and about 27 patients (75.7%) had EGFR mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has shown that the prognosis following radical surgical resection varies even among patients with various subtypes of the same disease stage and that the postoperative recurrence of lung adenocarcinoma may be related to its histologic subtype 6 . In 2011, The International Association for the Study of Lung Cancer, The American Thoracic Society, and the European Respiratory Society proposed a new histologic classification of lung adenocarcinomas that categorized invasive lung adenocarcinomas into five major growth patterns (lepidic, acinar, papillary, micropapillary [MIP], and solid), with a worse prognosis for patients with the MIP subtype and a better prognosis for those with lepidic 7–9 . The MIP component is characterized by tumor cells growing in papillary clusters without a fibrovascular core 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…The MIP component is characterized by tumor cells growing in papillary clusters without a fibrovascular core 6,7 . After surgical resection, patients with an MIP component are more likely to experience pleural and lymphovascular invasions, as well as lymph node or intrapulmonary metastases 8,10–13 . Therefore, the presence of an MIP component in patients with Stage I lung adenocarcinoma can lead to poorer overall survival (OS), disease‐free survival (DFS), and increased risk of recurrence 6,11,12 .…”
Section: Introductionmentioning
confidence: 99%